PROCRASTINATING TOGETHER: FLOCKING GRADUATE STUDENTS INTO GROUPS BASED ON A SHARED PROCLIVITY TO PROCRASTINATE. Issue 2 (2nd April 2020) - Harding, Lora Mitchell
ABSTRACT: Marketing instructors have long struggled with the issue of free-riding in groups. "Flocking" students based on shared motivation levels has been found to reduce free-riding among undergraduates, but this method may be less effective in graduate courses where student motivation is often more homogeneous. This article presents a modified flocking method whereby graduate students are flocked into groups according to their proclivity to procrastinate, such that students with a high (low) proclivity are matched with similar others. The results of a quasi-experiment show that graduate students flocked by procrastination proclivity (vs. motivation) report less free-riding and better perceived learning outcomes.